„Uniwerek” – opieka nad dziećmi w wieku do lat trzech. Od inspiracji do realizacji - Anna Godlewska-Zaorska; Bernadetta Olender-Jermacz (Problemy Wczesnej Edukacji)
This article describes experience gained during work with the project “Uniwerek”.  Our experience is presented in the light of narrative approach. In the narrative, we introduce how we have gone from inspiration to implementation of our project, about peculiar beginnings and everyday aspirations. “Uniwerek” is a nursery institution for children under the age of three. It has a caring, upbringing and educational role. It is located in the Kortowo campus. In the considerations presented, we used the sociocultural perspective, which showed our way of understanding the nature of the learning process, as well as defined the vision/ role of the child and tutor, educator, teacher and the environment in this space.